The pre-surgical factors that determine the decision to proceed to resection in children diagnosed with high-risk neuroblastoma in a resource limited setting. (3rd April 2023) - van Heerden, Jaques; Kruger, Mariana; Esterhuizen, Tonya Marianne; van Zyl, Anel; Hendricks, Marc; Cox, Sharon; Mangray, Hansraj; Poole, Janet; Naidu, Gita; Büchner, Ané; de Villiers, Mariza; du Plessis, Jan; et al.
Abstract: Surgical control has prognostic value in neuroblastoma (NB). Advanced NB is common at diagnosis in South Africa. We investigated the pre-surgery factors that influenced decisions to perform surgical resections. We included 204 patients with high-risk NB from a national retrospective study, who completed induction chemotherapy between 2000 and 2016. The median age was 32.4 months (IQR 15.1 − 53.5 months). Primary tumor resection was achieved in 76.9% of patients between 0-18 months of age, 51.8% between 18-60 months and 51.7% older than 60 months (p < 0.001). Only 43.2% of patients with distant metastatic disease had surgery done (p < 0.001). LDH was >750 U/L in 46.8% and ferritin >120 g/dL in 53.1% of those who had surgery (p = 0.005). The majority (80.4%), who had achieved post-induction metastatic complete remission (mCR), were operated, while 28.7% without mCR had surgery (p < 0.001). The long-term overall survival in patients with mCR and primary tumor resection was 36.5% compared to those with mCR without primary tumor resection (25.4%) and without mCR (≤3.0%)(p < 0.001). Age (p < 0.001), stage (p < 0.001), mCR (p < 0.001) and treatment setting (p < 0.001) were of prognostic significance. The tumor site and MYCN-amplification did not significantly predict resection rates. Post-induction mCR and stage were associated with surgical resection and five-year OS (p < 0.001) on multivariate analysis. Patients with high-risk NB who achieved mCR and had primary tumor resections are curable in limited resourced settings. Stage and post-induction mCR were significant variables that led to surgery. These variables should be included as indications in the management of metastatic NB in resource limited settings. TEACHING POINTS: High-risk neuroblastoma that achieved post-induction chemotherapy metastatic remission and have undergone resection, is curable, even in limited resource settings. Achieving metastatic complete remission was the only factor that significantly predicated if surgery was done. The age at diagnosis, stage and hospitals with expertise in neuroblastoma surgery were of prognostic significance in South Africa. If a patient with high-risk neuroblastoma achieves metastatic complete remission in a resource limited setting, it should be an indication for resection of the primary tumor.